Literatur Review : Aktivitas Antiacne Tanaman Daun Kelor (Moringa oleifera) Sebagai Kandidat Kosmetika Halal - Isna Primadana, Pradita Fiqlyanur (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Moringa leaves (Moringa oleifera) represent a valuable natural resource with numerous benefits, particularly in the field of cosmetics. These leaves exhibit remarkable pharmacological properties, notably antibacterial effects against acne-causing bacteria. Such antibacterial activity is attributed to the presence of secondary metabolites, including flavonoids, alkaloids, and tannins. From the perspective of Islamic jurisprudence, any substance derived from natural sources is considered halal; therefore, Moringa oleifera holds strong potential as a halal cosmetic ingredient. This study aimed to evaluate the antiacne activity of Moringa oleifera leaves as a prospective halal cosmetic agent. The research employed a literature review method using a narrative, unsystematic review model. The reviewed literature comprised scientific articles published between 2018 and 2022 in either Indonesian or English. A total of 1,104 articles were initially identified, of which 31 met the inclusion criteria. The findings revealed that Moringa oleifera leaves demonstrate significant antibacterial activity against acne-associated bacteria, including Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. This antibacterial potential is closely related to the presence of various secondary metabolites such as flavonoids, tannins, steroids, alkaloids, saponins, benzyl isothiocyanate, and benzyl glucosinolate.